Exploring Corporate Strategy / Text and Cases: Fifth Edition - Johnson Gerry; Scholes Kevan (Prentice Hall Europe, 1999)
This book remains the essential tool of Strategy Teaching. Preface, Introduction, Corporate Strategy: An Introduction, Strategic Management in Practice, Strategic Analysis, Analyzing the Environment, Resources and Competences and Strategic Capability, Stakeholder Expectations and Organizational Purposes, Strategic Choice, Bases of Strategic Choice, Strategic Options: Directions and Methods of Development, Strategy Evaluation and Selection, Strategic Implementation, Organization Structure and Design, Resource Allocation and Control, Managing Strategic Change, Case Studies, Glossary, General Index.